2019
DOI: 10.3390/atmos10110703
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Model Evaluation of Meteorological Drivers, Air Pollutants and Quantification of Emission Sources over the Upper Brahmaputra Basin

Abstract: The temporal distributions of meteorological drivers and air pollutants over Dibrugarh, a location in the upper Brahmaputra basin, are studied using observations, models and reanalysis data. The study aims to assess the performance of the Weather Research and Forecasting model coupled with chemistry (WRF-Chem), the WRF coupled with Sulfur Transport dEposition Model (WRF-STEM), and Copernicus Atmosphere Monitoring Service (CAMS) model over Dibrugarh for the first time. The meteorological variables and air pollu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 101 publications
(126 reference statements)
0
4
0
Order By: Relevance
“…In this kind of setup, we were able to overcome computational limitations in terms of storage and processing capacity. Both of the simulations (25 km and 4 km resolutions) used National Center for Environmental Prediction Final Analysis (NCEP-FNL) for the meteorological initial conditions [7,24], whereas boundary conditions for the simulation at WC/WRF25 used NCEP-FNL and the simulations at WC/WRF4 used meteorological data from WC/WRF25. In a similar way, the WC25 simulations used chemical boundary conditions from a global simulation model for ozone and related chemical tracers, version 4(Mozart-4) [33].…”
Section: Model Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…In this kind of setup, we were able to overcome computational limitations in terms of storage and processing capacity. Both of the simulations (25 km and 4 km resolutions) used National Center for Environmental Prediction Final Analysis (NCEP-FNL) for the meteorological initial conditions [7,24], whereas boundary conditions for the simulation at WC/WRF25 used NCEP-FNL and the simulations at WC/WRF4 used meteorological data from WC/WRF25. In a similar way, the WC25 simulations used chemical boundary conditions from a global simulation model for ozone and related chemical tracers, version 4(Mozart-4) [33].…”
Section: Model Setupmentioning
confidence: 99%
“…A previous study has indicated that the presence of aerosols can enhance or suppress rain over Asian regions [4]. The Indo-Gangetic Plain (IGP), which is known as a hotspot of anthropogenic pollution in South Asia [5][6][7], as well as the deserts of Rajasthan and middle east Asia [8], supply ample aerosols to the Himalayan region.…”
Section: Introductionmentioning
confidence: 99%
“…Barman and Gokhale ( 2019 ) reported enhanced BC mass concentration (BCC) over Guwahati city, mainly contributed by vehicular emissions. Saikia et al ( 2019 ) stated that open biomass burning is the region’s dominant source of BC and CO.…”
Section: Introductionmentioning
confidence: 99%
“…36 Only a few studies have reported the association of reanalysis data of carbonaceous aerosol mass concentrations with groundbased observations over South Asia. For example, Saikia et al 37 and Pathak et al 38 reported the association of ground-based measured BC with CAMS and MERRA-2 at Dibrugarh, located in India's northeast region. Prabhu et al 21 reported the association of ground-based measured BC with CAMS and MERRA-2 at Dehradun, located in the foothills of western Himalayas.…”
Section: Introductionmentioning
confidence: 99%